PERTANGGUNGJAWABAN NOTARIS PENGGANTI YANG MELAKUKAN PERBUATAN MELAWAN HUKUM DALAM MEMBUAT AKTA OTENTIK - ARIE HERMAWAN (PREMISE LAW JURNAL, 2017)
Illegal act committed by a Substitute Notary is basically divided into three categories: illegal act in civil case, in criminal case, and in Code of Ethics. Illegal act committed by a Substitute Notary in making authentic deeds is based on its type. According to UUJN (the Notarial Act), his liability in making authentic deeds is regulated in Article 33, paragraph (2) which confirms that a Notary’s liability as regulated in Article 15, Article 16, and Article 17 is also in effect on Substitute Notary. Minimizing the incidence rate of Substitute Notary’s illegal act includes preparing for knowledge, supervision, and strict legal sanction. The obstacles are lack of quality in legal provisions which can be concerned with a Substitute Notary’s illegal act, the absence of Monitoring Board, lack of awareness of law, and Substitute Notary’ bad knowledge. Keywords: Liability, Substitute Notary, Illegal Act, Authentic Deed